Mathematics for Computer Science - Arnold A.; Guessarian I (Prentice Hall, 1996)
This book looks at the mathematics which underpins the whole computer science. Preface, Sets and Functions, Ordered Sets, Recursion and Induction, Boolean Algebras, Logic, Combinatorial Algebra, Recurrences, Generating Series, Asymptotic Behavior, Graphs and Trees, Rational Languages and Finite Automata, Discrete Probabilities, Finite Markov Chains, Applications and Examples, Answers to Exercises, Index.